IMPLEMENTATION GAPS IN RENEWABLE ENERGY INTEGRATION: EVIDENCE FROM RURAL PRACTITIONERS IN BULGARIA, ESTONIA, SLOVENIA, AND SPAIN (TRAKIA JOURNAL OF SCIENCES, 2025)
PURPOSE: This study examines the implementation gaps between renewable energy policies and their practical application in rural agricultural and forestry sectors across four European Union member states. METHODS: Through a mixed-methods analysis of practitioner responses from Bulgaria, Estonia, Slovenia, and Spain, combined with recent policy developments, we identify critical barriers and successful strategies for rural renewable energy integration. RESULTS: The research reveals significant variations in policy effectiveness, with administrative complexity and community acceptance emerging as primary implementation challenges. Financial mechanisms show mixed effectiveness across countries, while energy community development remains constrained by regulatory gaps and local capacity limitations. CONCLUSIONS: The findings indicate that successful implementation requires context-sensitive approaches that address specific regional challenges while maintaining policy coherence at multiple governance levels. The study provides evidence-based recommendations for policymakers at EU, national, and regional levels to enhance renewable energy integration in rural areas.